(untitled) (Tạp chí Y học Cộng đồng, 2026)
Objectives: To evaluate the early outcomes of breast reconstruction using the extended latissimus dorsi flap (eLDF) in patients with breast cancer treated at K Hospital. Subjects and Methods: A retrospective descriptive study was conducted on 41 breast cancer patients who underwent breast reconstruction using the extended latissimus dorsi flap from April 2024 to October 2025 at the Department of Breast Surgery, K Hospital. Study variables included clinical characteristics, surgical methods, surgical outcomes, intraoperative and postoperative complications, cosmetic outcomes, and postoperative quality of life. Results: The mean patient age was 41 ± 2.3 years, and the mean BMI was 23.5 ± 0.8. The mean clinical tumor size was 2.7 ± 0.6 cm. Modified radical mastectomy was the most commonly performed procedure, accounting for 83.4% of cases. The conventional eLDF technique was predominantly used (59.5%). The mean operative time was 160 ± 23.3 minutes, and the mean estimated blood loss was 85.2 ± 5.6 mL. The mean postoperative hospital stay was 12.5 ± 0.6 days. The most common early complication was donor-site seroma in the back region (28.6%). Partial flap necrosis occurred in 4.8% of patients. No cases of total flap necrosis were recorded. Most patients achieved favorable cosmetic outcomes and were satisfied with the appearance of the reconstructed breast. Conclusion: Breast reconstruction using the extended latissimus dorsi flap is a safe and feasible technique that provides favorable cosmetic outcomes with acceptable complication rates. This method is particularly suitable for patients who are not candidates for microsurgical flap reconstruction or who have poor chest wall tissue quality.